2023
DOI: 10.4251/wjgo.v15.i1.143
|View full text |Cite
|
Sign up to set email alerts
|

Short-term efficacy and influencing factors of conventional chemotherapy combined with irinotecan in patients with advanced gastric cancer

Abstract: BACKGROUND Gastric cancer is one of the most common cancers worldwide, with a 5-year survival rate of only 20%. The age of onset of gastric cancer is in line with the general rule of cancer. Most of them occur after middle age, mostly between 40 and 60 years old, with an average age of about 50 years old, and only 5% of patients are under 30 years old. The incidence of male is higher than that of female. AIM To investigate the short-term efficacy and influencing factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…At the same On the basis of conventional chemotherapy regimen, this report compared the efficacy of camrelizumab combined with raltitrexed and raltitrexed alone in the therapy of advanced gastric cancer and postoperative recurrent and metastatic gastric cancer, the results corroborated that the ORR and DCR of the survey subgroup were 54.76 % and 80.95 %, which were boosted than those of the control subgroup (31.58 % and 57.89 %), indicating that camrelizumab monoclonal antibody united with raltitrexed could improve the short-term outcome of advanced gastric cancer. Wang et al [24] also found that after the observation group was treated with irinotecan on the basis of chemotherapy in the control group, the short-term effect of the observation group was better than that of the control group. Systemic chemotherapy is the main therapy for advanced gastric cancer, but conventional chemotherapy program with platinum+fluorouracil is not effective and the curative outcome is limited [25] .…”
Section: Resultsmentioning
confidence: 99%
“…At the same On the basis of conventional chemotherapy regimen, this report compared the efficacy of camrelizumab combined with raltitrexed and raltitrexed alone in the therapy of advanced gastric cancer and postoperative recurrent and metastatic gastric cancer, the results corroborated that the ORR and DCR of the survey subgroup were 54.76 % and 80.95 %, which were boosted than those of the control subgroup (31.58 % and 57.89 %), indicating that camrelizumab monoclonal antibody united with raltitrexed could improve the short-term outcome of advanced gastric cancer. Wang et al [24] also found that after the observation group was treated with irinotecan on the basis of chemotherapy in the control group, the short-term effect of the observation group was better than that of the control group. Systemic chemotherapy is the main therapy for advanced gastric cancer, but conventional chemotherapy program with platinum+fluorouracil is not effective and the curative outcome is limited [25] .…”
Section: Resultsmentioning
confidence: 99%